Consumer Protection Against Distribution Of Dangerous Cosmetics Sold Online In Indonesia, Malaysia And The Philippines - Andira, Ayu; Muhammad, Danang Wahyu (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
There are still many dangerous ingredients in the circulation of cosmetics, such as various brands and substances containing dangerous ingredients. This action occurred in various Asian countries, including Indonesia, Malaysia, and the Philippines. Many countries have created regulations and provisions regarding Consumer Protection. Thus, this research first analyses how the laws of Indonesia, Malaysia, and the Philippines compare consumer protection with the online distribution of dangerous cosmetic materials. Second, what are the legal and regulatory efforts for consumer protection regarding the online distribution of dangerous cosmetic products in Indonesia, Malaysia and the Philippines? The research method uses normative juridical, which examines the comparison of consumer protection between Indonesia, Malaysia and the Philippines so that it can become a reference for everyone's behaviour. In reality, Indonesia adheres to a Civil Law system. In contrast, Malaysia adheres to a Common Law system. Still, interestingly, the Philippines applies a Civil Law and Common Law system. Efforts to protect consumers against cosmetic products with dangerous ingredients can implement the ASEAN Regional Guidelines on Competition Policy (Regional Guidelines). It can also adopt the ASEAN Cosmetic Directive (ACD) regulations.